Time and space in the classroom - lessons from Germany and Sweden - Jakob Billmayer (Taylor & Francis Group, 2019)
In this study, aspects of space and time in German and Swedish classrooms are observed and compared to characterize differences and similarities in classrooms and lessons in different contexts. The organization and control of individuals and their actions in relation to time and space are analysed using categories derived from Discipline and Punish utilizing a model of empirically informed typification analysis. The empirical data consist of field studies conducted by participant observation in German and Swedish classrooms. The type of classroom found in Germany is characterized by fixed boundaries and frameworks. The lessons are uniform, and class time is structured so as to minimize the number of interruptions between different activities. Boundaries are less clear in the type of classroom found in the Swedish material, where the classroom is just one of many places for teaching and learning. The lessons and schedules are less uniformly structured, and a lot of time is spent discussing the plans for instruction.